PKM OLAHAN TELUR BEBEK UNTUK MEMENUHI KEBUTUHAN GIZI DAN MENINGKATKAN PENDAPATAN MASYARAKAT DESA RUMAH SUMBUL - Rimbawati Rimbawati; Rahmad Bahagia Siregar (Universitas Sanata Dharma, 2019)
Rumah Sumbul village is one of the disadvantaged villages in Deli Serdang district due to the fact that the majority of the villagers are rubber farmers who experienced a significant decline in selling prices in the past three years ago. The increasingly heavy economic pressures as a result of the decline in rubber prices forced people to change professions into laborers at oil palm plantations to meet their daily needs. This condition affects the nutritional needs of the community directly. Based on the statement of the Sumbul Village Chief, Mr. Makmur Barus, to the Team, there were 30 people raising ducks and joined in three groups of poultry scattered in several hamlets. But the lack of knowledge in producing processed duck eggs makes all citizens just sell their eggs at a price of IDR 2,000/grains. Based on these problems the PKM aimed to conduct training in making various flavored salted egg preparations and provide training in production and marketing management. Accordingly, partners were able to produce various types of processed duck eggs as souvenirs typical of Tigajuhar for sale to traditional markets and tourist attractions in the region, such as Lake Linting, Kawah Putih and Sibiru-blue beach, which is approximately 2 to 5 km from the Partner's location at a price of IDR 4,000/grains. It is expected that the locals can increase their per capita income while at the same time meeting the nutritional needs of the community.